متطلبات تطوير نظم المعلومات في الوحدات الاقتصادية من خلال النظام المتكامل للمعلومات المحاسبية و الادارية - زياد هاشم يحيى (PROSPECTIVE RESEARCHES, 2023)
The present research tackles the issue of developing the accounting information system in the economic units via designing an integrated system for management and accounting system. This system should be able to achieve the coordinative and integrative relationships among the subunits which exist in the economic units represented by Accounting Information System and Management Information System. A set of necessary requirements have been identified to apply the integrated system, viz. accounting management information system, central database, technological system and devices, and qualified personnel in accounting, management, and computers.